La motricidad cotidiana en la cultura corporal de niños y niñas de quinto grado de una institución educativa de la ciudad de Medellín (2012)
ABSTRACT: This article shows the results of the everyday motor skills dimension that were explored in the macro research “Body culture among children in fifth grade of primary education at Institución Educativa Monseñor Francisco Cristóbal Toro from Aranjuez neighborhood in Medellín City”. Its purpose is to understand the particular of the body culture of children in the context of that educational institution. This qualitative-nature research, specifically from the ethnographic approach, involves the immersion into daily school life and how the motor skills are immersed into it. It developed the fieldwork in the school setting in constant interaction with the studied population.